Major Bioactive Prenylated Flavonoids from Humulus lupulus L., Their Applications in Human Diseases and Structure-Activity Relationships (SAR) – A Review - Ferah Comert Onder; Sevil Kalin; Nebahat Sahin; Gulce Davutlar; Khaled A.N. Abusharkh; Ozlem Maraba; Rabia Selina Hal; Mehmet Ay; Lutfun Nahar; Satyajit D. Sarker (Pharmaceutical Sciences, 2024)
In recent years, the incidence of cancers, inflammatory diseases, Alzheimer’s disease, glucose metabolism disorder and diabetes has increased alarmingly which demands more research into the discovery of new drug candidates to treat these human diseases. Main phytochemicals from Humulus lupulus L. (hops) have been demonstrated to have positive impacts on human health, and prenylated flavonoids are one of the major groups of bioactive phytochemicals found in this plant. Thus, this review summarizes the role of major prenylated components in hops in human diseases including cancer, inflammation and viral infections. In silico studies of prenylated bioactive compounds against various drug targets such as histone deactylases (HDACs), sirtuins (SIRTs), and acetylcholinesterase (AChE), and the molecular molecular interactions between protein and ligand have also been included. Furthermore, the structure-activity relationships (SAR) studies on these compounds are highlighted. This review concludes that the prenylated phytochemicals from H. lupulus L., including xanthohumol (XN), isoxanthohumol (IXN), 8-prenylnaringenin (8-PN) and 6-prenylnaringenin (6-PN), have promising roles in human health and may contribute to new drug discovery and development.